Anti-PD1 does not improve pyroptosis induced by γδ T cells but promotes tumor regression in a pleural mesothelioma mouse model - Lui, Ka Sin; Ye, Zuodong; Chan, Hoi Ching; Tanaka, Yoshimasa; Cheung, Allen Ka Loon (Frontiers in Immunology, 2023)
Mesothelioma is an aggressive tumor in the pleural cavity that is difficult to treat. Diagnosis is usually late with minimal treatment options available for the patients and with unfavorable outcomes. However, recent advances in immunotherapy using gamma-delta T cells may have potential against mesothelioma, given its ample tumoricidal and tumor-migratory properties could allow its infiltration to the widespread tumor mass. Thus, we hypothesize that Vδ2 T cells can perform cytotoxic activities against mesothelioma especially when combined with immune checkpoint blocker against PD-1. Indeed, our data demonstrated that Vδ2 T cells killing mesothelioma can be enhanced by anti-PD-1 antibody in vitro, especially for high PD-1 expressing cells, and in vivo in the intrapleural mesothelioma mice model established by us. Adoptive transfer of Vδ2 T cells into these mice leads to tumor regression by 30-40% compared to control. Immunofluorescence of the tumor section confirmed infiltration of Vδ2 T cells into the tumor, especially to cells with BTN2A1 expression (a Vδ2 T cell activating molecule) despite PD-L1 co-localization. Interestingly, these cells co-expressed cleaved gasdermin D, suggesting that pyroptosis was induced by Vδ2 T cells. This was verified by Vδ2 T/mesothelioma co-culture experiments demonstrating membrane blebbing morphology, increased cleaved caspase-3 and gasdermin E, and upregulated IL-1b and IL-18. However, anti-PD-1 treatment had no advantage for PD-1 high expressing Vδ2 T cells in promoting pyroptosis. Taken together, our work demonstrated that Vδ2 T cells combined with anti-PD-1 antibody can be developed as a potential combination immunotherapy for mesothelioma.